Induction Methotrexate, Cisplatin, and 5-Fluorouracil Versus Cisplatin and 5-Fluorouracil Followed by Radiotherapy in Pediatric Nasopharyngeal Carcinoma: A Retrospective Analysis in a Tertiary Cancer Center. Issue 8 (November 2017) - Al Mousa, Abdelatif; Abu-Hijlih, Ramiz; Salem, Ahmed; Sultan, Iyad; Mula-Hussain, Layth; Ismael, Taleb; Mohamad, Issa
Abstract : Purpose: The purpose of this study is to compare treatment outcomes of methotrexate, cisplatin, and 5-fluorouracil (MPF) or cisplatin and 5-fluorouracil (PF) in pediatric NPC patients treated with sequential chemoradiotherapy. Patients and Methods: A total of 25 patients aged 18 years or below with stage II-IV NPC treated with IC using PF (n=16) or MPF (n=9) followed by radiotherapy between 2003 and 2009 were retrospectively reviewed. Radiotherapy dose was 61.2 to 66.6 Gy to the gross disease. Age, stage, radiation dose, and chemotherapy regimen were tested as prognostic factors for event-free survival (EFS) and overall survival (OS) on univariate and multivariate analyses. Results: The median age at diagnosis was 13.3 years. All patients completed planned chemotherapy. All patients who received MPF achieved PR whereas 15 patients (93.8%) who received PF achieved PR ( P =1). There were no differences in EFS (68.75% vs. 66.67%; P =0.84) and OS (81.25% vs. 66.67%; P =0.39) at 5 years between PF and MPF, respectively. On multivariate analysis, only tumor stage (IV vs. II-III) predicted worse OS (hazard ratio, 10.3; 95% confidence interval, 1.197-88.974) but not EFS (hazard ratio, 4.805; 95% confidence interval, 0.95-24.336). Distant metastases was the predominant site of failure, seen in 5 patients (20%). Conclusions: Omission of methotrexate from the induction chemotherapy regimen did not affect treatment outcome.